CIPP-Based Evaluation of Physical Education Learning Management in Junior High Schools in Praya Tengah - Riski, Robi Maulana; Kurniawan, Edi; Irmansyah, Johan; Muammar, Muammar (Sportify Journal, 2025)
Uneven physical education learning management may affect the quality of planning, implementation, and assessment in schools. This study aimed to evaluate physical education learning management across the context, input, process, and product components in public junior high schools in Praya Tengah District. A quantitative descriptive evaluative approach using the CIPP model was employed. Data were collected through questionnaires, observations, structured interviews, and documentation involving students, principals, and physical education teachers. The findings showed that, based on students’ perceptions, SMPN 1, SMPN 3, and SMPN 4 Praya Tengah were categorized as very good, while SMPN 2 was categorized as good. Based on principals’ and teachers’ perceptions, all schools were categorized as very good. The process component showed relatively strong performance; however, perception gaps emerged between students and school personnel, particularly at SMPN 2. Physical education learning management is generally good but requires further improvement in student learning experiences, facilities, teaching methods, and authentic assessment.